Do direito aos direitos: uma análise do discurso de crianças e adolescentes em medida protetiva de acolhimento institucional - Junqueira, Luciana Villela (2012)
This dissertation is part of a prospect of recognition of rights and safeguards of children and adolescents in protective measure of institutional care. The aim is thus to explore the point of view of each one of these subjects, using the resources of the privileged Oral History, as well as some legal frameworks, such as the implementation of Individual Service Plans (IAP) and the realization of Concentrated Audiences. Therefore, based on a qualitative approach, 06 (six) interviews took place in 03 (three) Host Institutions located in the city of São Paulo. In these meetings, the children and teenagers selected for the study were able to rescue a few moments of their lives, besides expressing opinions and impressions about their relationships with family, the shelter and the Judiciary. The basis of the study approached concepts such as the formation and breakup of affective bonds, the listening space, the importance of safety nets and transdisciplinary movement that seeks to transcend the closed universe of the science of law and to bring out the multiplicity of other ways of knowledge as key aspects for the recognition and expansion of the rights of children and adolescents in protective measure of institutional care. The analysis of these interviews revealed the importance of ethics the care in relationships and the look that not only sees, but sees these children as authentic, once these children and adolescents are not only seen as objects to be known, but as subjects recognized and legitimized, the relationship established with them goes up to a new level, supported by the realization of true human experience, endowed with social and cultural experiences that are so rich in meanings. The research also indicated that the Individual Service Plans and Concentrated Audiences really can bring important contributions to the promotion of the rights and guarantees of these children and adolescents, once the professionals who support its implementation do so in an integrated, linear and mainly humanized way